KATHERINE MANSFIELD IS A MASTER OF SHORT STORIES - Sitorabonu Ataullayeva (Scholar Express Journal, 2023)
This article is dedicated to the life and work of the famous New Zealand writer Catherine Mansfield. Her life is exemplary. Her diaries reflect her perseverance and tenacity. It teaches everyone the secrets of overcoming life’s hardships. It inspires them to achieve their goals. Her short stories have a special place in world literature due to the perfection and uniqueness of their forms of artistic expression. In them, the writer penetrates deep into the human psyche and is able to impress and follow the reader
Keywords: Story; Image; Tradition; Literary Influence